(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
We prove, the existence of coincidence points and common fixed points for four self- mappings satisfying a generalized contractive condition without normal cone in cone metric spaces. Our results generalize several well-known recent and classical results.